Characterizing plasma lipid species in metabolic dysfunction associated steatotic liver disease in persons with type 1 diabetes - Adeyinka Taiwo; Himani Thakkar; J. Alan Maschek; James Cox; Scott A. Summers; Diana Jalal; Ayotunde Dokun; William I. Sivitz; Bhagirath Chaurasia (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is the hepatic manifestation of metabolic syndrome. Hepatic lipotoxicity and inflammation are two key factors driving progression of steatosis to metabolic dysfunction-associated steatohepatitis (MASH). The presence of MASH increases the risk of cardiovascular events, cirrhosis, hepatocellular carcinoma (HCC) and non-liver malignancies. Although MASLD and lipid species have been extensively examined in persons with type 2 diabetes, much less is known in type 1 diabetes. We examined the association of key lipid species with MASLD in individuals with type 1 diabetes. We designed a cross-sectional study of 30 participants with type 1 diabetes recr1uited from our institutional diabetes clinics. All participants had fasting blood drawn for targeted lipidomics and underwent a FibroScan. Those with steatosis score of ≥ 248 as determined by controlled attenuation parameter (CAP) were categorized as cases (n = 17); those with steatosis score < 248 were categorized as controls (n = 13). BMI was significantly higher in cases than controls (P = 0.0007) and used significantly higher 24-h insulin doses than controls (P = 0.004). Cases displayed significantly higher circulating levels of total ceramides (P = 0.02), diacylglycerols (P = 0.0009) and triacylglycerols (P = 0.0004). The two groups displayed similar levels of hexosylceramides, dihydrosphingomyelins, sphingomyelins, and phosphatidylcholines. Similar to previous findings, numerous sphingolipids species, diacylglycerols, and triacylglycerols were found to correlate positively with higher BMI and 24-h insulin dose. Total circulating dihydroceramides, ceramides, diacylglycerols, and triacylglycerols levels significantly correlated with steatosis score (P < 0.05). None of the lipid species correlated with fibrosis score. These results suggest that persons with type 1 diabetes and MASLD have a higher BMI, are likely to be insulin resistant, and display elevated circulating levels of dihydroceramides, ceramides, diacylglycerols, and triacylglycerols, which are strongly associated with the pathogenesis of steatotic liver disease.